2015
DOI: 10.3892/or.2015.4405
|View full text |Cite
|
Sign up to set email alerts
|

10-Gingerol inhibits proliferation and invasion of MDA-MB-231 breast cancer cells through suppression of Akt and p38MAPK activity

Abstract: In the present study, we investigated the roles and molecular mechanism of 10-gingerol, a phenolic compound isolated from Zingiber officinale, in regulating cell proliferation and invasion of MDA‑MB‑231 breast cancer cells. 10-gingerol treatment inhibited cell proliferation through downregulation of cell cycle regulatory proteins such as cyclin-dependent kinases and cyclins, and subsequent induction of G1 phase arrest. In addition, 10‑gingerol treatment blocked cell invasion in response to mitogenic stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 35 publications
1
29
0
2
Order By: Relevance
“…These effects are mediated by EGFR and b1-integrin suppression. The results presented in this study are in agreement with previous studies demonstrating that [10]-gingerol presented antitumor activities in MDA-MB-231 breast cancer cells, which are mediated by EGFR suppression and inactivation of Akt and MAPK activities [Joo et al, 2016].…”
Section: Discussionsupporting
confidence: 93%
“…These effects are mediated by EGFR and b1-integrin suppression. The results presented in this study are in agreement with previous studies demonstrating that [10]-gingerol presented antitumor activities in MDA-MB-231 breast cancer cells, which are mediated by EGFR suppression and inactivation of Akt and MAPK activities [Joo et al, 2016].…”
Section: Discussionsupporting
confidence: 93%
“…In a syngenic mouse model of spontaneous breast cancer metastasis, gingerol (5 mg/ kg) treatment induced caspase-3 activation and inhibited the orthotopic tumor growth as well as metastasis of mouse brainmetastatic 4T1Br4 mammary tumor cells to multiple organs such as lung, bone and brain (Martin et al, 2017). Likewise, Joo and colleagues (Joo et al, 2016) reported inhibition of lungmetastatic, MDA-MB-231 human breast cancer cell proliferation, and invasion by [10]-gingerol through suppression of Akt, p38MAPK, and epidermal growth factor receptor. The detailed protective and therapeutic potential of gingerol in cancer is reviewed in de Lima et al (2018).…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 93%
“…The inserts were fixed with methanol, and using a cotton‐tipped swab, the non‐invasive cells were removed from the top of the membrane. After staining with 0.04% Giemsa staining solution, the numbers of invasive cells (mean ± standard deviation) were determined from six different fields using ×200 objective magnification …”
Section: Methodsmentioning
confidence: 99%